Organic and mineral fertilization, respectively, increase and decrease the development of external mycelium of arbuscular mycorrhizal fungi in a long-term field experiment - Gryndler, M; Larsen, J; Hršelová, H; Řezáčová, V; Gryndlerová, H; Kubát, J (Mycorrhiza, 2006)
Effects of long-term mineral fertilization and manuring on the biomass of arbuscular mycorrhizal fungi (AMF) were studied in a field experiment. Mineral fertilization reduced the growth of AMF, as estimated using both measurements of hyphal length and the signature fatty acid 16:1omega5, whereas manuring alone increased the growth of AMF. The results of AMF root colonization followed the same pattern as AMF hyphal length in soil samples, but not AMF spore densities, which increased with increasing mineral and organic fertilization. AMF spore counts and concentration of 16:1omega5 in soil did not correlate positively, suggesting that a significant portion of spores found in soil samples was dead. AMF hyphal length was not correlated with whole cell fatty acid (WCFA) 18:2omega6,9 levels, a biomarker of saprotrophic fungi, indicating that visual measurements of the AMF mycelium were not distorted by erroneous involvement of hyphae of saprotrophs. Our observations indicate that the measurement of WCFAs in soil is a useful research tool for providing information in the characterization of soil microflora.
Keywords: mycelium; Mycorrhizae; Minerals; biologické markery; Colony Count, Microbial; Manure; Biomarkers; hnůj; mastné kyseliny; počet mikrobiálních kolonií; Soil Microbiology; Spores, Fungal; Medicago sativa; Hyphae; Fatty Acids; Soil; spory hub; roční období; Seasons; Mycelium; minerály; půdní mikrobiologie; půda; mykorhiza; hyfy